AB0797 Intake Of Cod Liver Oil is Associated with Lower Body Mass Index in Psoriatic Arthritis Patients. (9th June 2015) - Michelsen, B.; Diamantopoulos, A.P.; Semb, A.G.; Kavanaugh, A.; Haugeberg, G.
Abstract : Background: Higher rates of obesity in psoriatic arthritis (PsA) than in other inflammatory joint diseases have been described 1 . Body mass index (BMI) is demonstrated to be inversely associated with circulating 25(OH) vitamin D levels 2 . Low vitamin D may promote lipogenesis in adipocytes 2 . On the other hand, obesity has been suggested to lead to more storage of vitamin D in adipose tissue 3 . Vitamin D supplementation through intake of cod liver oil is a cultural norm in Norway. Usually one spoonful a day is taken, giving a supplement of approximately 400 IU vitamin D. Objectives: To explore if an association between daily cod liver oil intake and BMI in PsA. Methods: PsA patients visiting an outpatient clinic were consecutively recruited. All patients fulfilled the CASPAR criteria. Extensive data collection was performed including a nutritional questionnaire. Correlation analyses were performed by use of Pearson correlation. Unadjusted comparisons were performed with independent t-test. Adjusted comparisons were performed with General Linear Models first adjusted for age and gender, further for age, gender, smoking, physical exercise, education duration, use of alcohol last 12 months and Disease Activity Index for psoriatic arthritis (DAPSA). Results: Among the 100 included patients mean (SD) age was 51.6 years (9.9), disease duration 9.5 years (6.7), education duration 13.0 years (3.4), BMI 28.6 kg/m 2 (4.6), DAPSA 19.6 (15.0), 55% were female, 16% were current smokers, 64% drank alcohol at least once a month the last 12 months. BMI was inversely correlated to daily cod-liver oil consumption (τ = -0.25, p=0.011), but not to consumption of sausages/hamburgers, pasta/rice, whole milk, fatty fish, sweet beverage, chocolate, daily cups of filter coffee, physical exercise, education duration, omega-3 tablets or DAPSA. The bivariate correlations between the independent variables were less than 0.3. The PsA patients who had a daily consumption of cod liver oil (16%) had significantly lower BMI compared to the PsA patients who did not consume cod-liver oil (84%), both in the unadjusted and the adjusted analyses (Table ). Conclusions: In our cohort of PsA patients who consumed cod-liver oil daily, BMI was significantly lower compared to the patients not consuming cod-liver oil. This difference remained significantly lower after adjusting for potential confounders including different lifestyle factors. Further studies in larger patient samples are warranted to confirm our findings. References: Mok CC et al.Prevalence of atherosclerotic risk factors and the metabolic syndrome in patients with chronic inflammatory arthritis.Arthritis Care Res 2011;63:195-202. Mai XM et al.Cross-sectional and prospective cohort study of serum 25-hydroxyvit. D level and obesity in adults:the HUNT study.Am J Epidemiol 2012;175:1029-36. Holick MF.Vitamin D deficiency.N Engl J Med.2007;357:266-81. Disclosure of Interest: None declared